Design and development of expert systems and neural networks - Medsker, Larry (Macmillan ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1994)
This book gives readers and practitioners the tools they need to develop appropriate applications and systems. It also explores managing and institutionalizing expert system development and usage.